Business mathematics - Pasion, Dante (Mandaluyong City, Philippines : National Book Store, 2004)
It is designed to give business students basic application of mathematics in business of the various field of interest.
Preface -- Introduction -- CHAPTER 1. Checking answers of the basic operations -- 2. Operations with decimals -- 3. Fractions -- 4. Percent in Business -- 5. Employees compensation -- 6. Buying and Selling -- 7. Simple interest -- 8. Compound interest -- 9. Depreciation -- 10. Income statement -- 11. Bank reconciliation.
Includes index.
Keywords: BUSINESS MATHEMATICS